Improving Outcomes in Tendon Repair: A Critical Look at the Evidence for Flexor Tendon Repair and Rehabilitation. Issue 6 (December 2016) - Khor, Wee S.; Langer, Martin F.; Wong, Richard; Zhou, Rui; Peck, Fiona; Wong, Jason K. F.
Abstract : Learning Objectives: After reading this article, the participant should be able to: 1. Appreciate the variation and evolution of flexor tendon management 2. Know how to assess the patient who presents with a flexor tendon laceration. 3. Understand the biology of repairing flexor tendon lacerations. 4. Appreciate the technical challenges in flexor tendon repair relating to different zones. 5. Understand the rationale of postoperative hand therapy. 6. Have an overview of the types of secondary tendon surgery. Background: Flexor tendon injury constitutes a considerable trauma workload for hand surgeons, and a vast amount of research is dedicated toward improving outcomes in tendon repair. This Continuing Medical Education article aims to provide an up-to-date evidence-based outline of flexor tendon surgery in the hand. Methods: The authors reviewed the literature on flexor tendon repairs to include a balanced overview of the experimental and clinical research. For each section, the best levels of evidence were assessed in the context of past research to provide a comprehensive opinion on best management. Results: The review highlights current trends in flexor tendon surgery, clinical assessment, anesthetic technique, surgical approach, repair technique, and rehabilitation. Carefully selected illustrations, figures, tables, and video have been used to supplement the findings of the review. Conclusions: Early active mobilization remains the only long-term proven strategy to improve outcomes. Incorporating intraoperative mobilization using "wide-awake" surgery could emerge to further improve tendon outcomes. Good surgical approach, meticulous surgery, up-to-date physiotherapy regimens, and patient education remain the cornerstone of obtaining best outcomes. Abstract : Related Video Content is Available Online.